CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

The solution for the equations c1x + b1y + a1 = 0 and  c2x + b2y + a2 = 0 is

S1 :x = (b1a2b2a1)(c1b2c2b1)

S2 :  y =(c1a2c2a1)(a1b2a2b1)


  1. S1 and S2 are true

  2. S1 and S2 are false

  3. S1 is true but S2 is false

  4. S1 is false but S2 is true


Solution

The correct option is C

S1 is true but S2 is false


S1 : x = (b1a2b2a1)(c1b2c2b1) 

S2 : y = (c1a2c2a1)(c2b1c1b2)

flag
 Suggest corrections
thumbs-up
 
0 Upvotes



footer-image